Twentieth-century music in the West an introduction - Perchard, Tom 1976-; Graham, Stephen 1982-; Rutherford-Johnson, Tim 1977-; Rogers, Holly ca. 20./21. Jh (Cambridge University Press, 2022)
This is the first introductory survey of western twentieth-century music to address popular music, art music and jazz on equal terms. It treats those forms as inextricably intertwined, and sets them in a wide variety of social and critical contexts. The book comprises four sections - Histories, Techniques and Technologies, Mediation, Identities - with 16 thematic chapters. Each of these explores a musical or cultural topic as it developed over many years, and as it appeared across a diversity of musical practices. In this way, the text introduces both key musical repertoire and critical-musicological approaches to that work. It historicises music and musical thinking, opening up debate in the present rather than offering a new but closed narrative of the past. In each chapter, an overview of the topic's chronology and main issues is illustrated by two detailed case studies
Title from publisher's bibliographic system (viewed on 22 Sep 2022)
Introduction -- Part 1. Histories. Place and space, local and global ; Modernism ; Postmodernism ; Canons -- Part 2. Techniques and technologies. Work and notation ; Rhythm and time ; Harmony ; Instruments -- Part 3. Mediation. Recording and production ; Copyright and the music industry ; States and markets ; Music and the Moving Image -- Part 4. Identities. Gender and sexuality ; Race and ethnicity ; Audiences, class and consumption ; Centres and peripheries
Keywords: Geschichte 1900-2000; Music / 20th century / History and criticism; Music / 20th century / Analysis, appreciation; Music trade / History / 20th century; Music / Social aspects / History / 20th century; Technologie; Identität -- Motiv; Musiktheorie; Musiksoziologie; Musikwirtschaft; Musik; Westliche Welt